Day-Butterfly species composition (Lepidoptera, Rhopalocera) on high mountain tops of the Hoang Lien Natural Reserve, Lao Cai province - Lien, Vu Van (Academia Journal of Biology, 2015)
The day-butterfly species composition on high mountain tops of the Hoanglien natural reserve was surveyed from 1998 to 2001. There are 70 day-butterfly species recorded on high mountain tops, of which one is a rare species Teinopalpus imperialis (listed in the Red List of IUCN and in CITES) with only one female specimen collected. This species and some other species such as Meandrusa sciron are restricted to mountain tops. Two species found in this area are firstly recorded for Vietnam. The habitats on the high mountain tops are important to butterfly species, especially to mountain restricted species. Such habitats are needed to be conserved for mountainous species and many other visitor butterflies.